2012
DOI: 10.1590/s0103-21002012000600018
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das condições de uso de esfigmomanômetros em serviços hospitalares

Abstract: Objective: To evaluate the conditions of sphygmomanometers in use at public and private hospitals. Methods: A descriptive study using a quantitative approach, undertaken in four major hospitals in the State of São Paulo, in the period between 2009 and 2010. The aneroid manometers were tested against a calibrated mercury manometer. They were considered out of calibration when the differences were ≥ 4 mmHg. Results: We assessed 162 sphygmomanometers (78 in a public hospital and 84 from philanthropic and private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…These evidences are based on a study on the evaluation of the conditions of the use of sphygmomanometers in health services, which revealed that most respondents (76.6%) did not know how often the aneroid apparatus should be calibrated. 7 It is also worth noting that 0% of the participants knew how to evaluate the calibration of the automatic devices because they were not available in the institution. Therefore, since there is a current tendency to replace aneroid devices by automatic devices, it would be extremely important that trainings are carried out in order to prepare professionals to deal with this novelty.…”
Section: Discussionmentioning
confidence: 99%
“…These evidences are based on a study on the evaluation of the conditions of the use of sphygmomanometers in health services, which revealed that most respondents (76.6%) did not know how often the aneroid apparatus should be calibrated. 7 It is also worth noting that 0% of the participants knew how to evaluate the calibration of the automatic devices because they were not available in the institution. Therefore, since there is a current tendency to replace aneroid devices by automatic devices, it would be extremely important that trainings are carried out in order to prepare professionals to deal with this novelty.…”
Section: Discussionmentioning
confidence: 99%